Recycling policy and program strategies from households' perspectives: a case study in Muar Royal City - Moh, Yiing Chiee; Abdul Manaf, Latifah (Faculty of Science, University of Malaya, 2016)
Developing areas in Malaysia face similar concerns that landfill sites are too close for comfort and effort to minimise disposal to landfills are minimal despite the potential and opportunities to recycle. This paper provides an introspective insight about households' expectations on recycling policy and program strategies in local community via questionnaire survey conducted based on stratified random selection. Findings revealed that programs focusing on convenience, knowledge, and monetary benefit receive significantly higher support from households. Terms such as inconvenience, nuisance, and troublesome are commonly brought up in household recycling. They are less tolerating when it comes to imposing extra fees or charges. In order to understand how these households are influenced whether to recycle or otherwise, majority claimed that they are most likely to make their own decision on that which could possibly distinctively be a group of committed recyclers or non-recyclers. There are individuals who might be susceptible to changing their behaviour, which explains the role of other factors motivating recycling behaviour is fundamental. These findings extend our understanding on the perspectives of households towards recycling and based on the findings, this study proposed recommendations for possible implementations in the local municipalities to extend the potentials in achieving recycling community.